The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neuroimage.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Extracting multidimensional stimulus-response correlations using hybrid encoding-decoding of neural activity

Abstract: In neuroscience, stimulus-response relationships have traditionally been analyzed using either encoding or decoding models. Here we propose a hybrid approach that decomposes neural activity into multiple components, each representing a portion of the stimulus. The technique is implemented via canonical correlation analysis (CCA) by temporally filtering the stimulus (encoding) and spatially filtering the neural responses (decoding) such that the resulting components are maximally correlated. In contrast to exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 73 publications
6
92
1
Order By: Relevance
“…One is the fronto-central region, and the other is the parietal-occipital region. This is in line with other related works that estimate spatial filters based on speech processing (Dmochowski et al, 2018) and those that shows the topography of speech processing in the brain Hjortkjaer et al, 2018;O'Sullivan et al, 2015). For the second component we did not find any significant clusters.…”
Section: ) Data Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…One is the fronto-central region, and the other is the parietal-occipital region. This is in line with other related works that estimate spatial filters based on speech processing (Dmochowski et al, 2018) and those that shows the topography of speech processing in the brain Hjortkjaer et al, 2018;O'Sullivan et al, 2015). For the second component we did not find any significant clusters.…”
Section: ) Data Analysissupporting
confidence: 93%
“…This, however, requires repeated trials, which renders it impractical for many EEG applications (although for MEG data, a few trials are typically enough for DSS to obtain a useful dimensionality reduction and denoising (Akram et al, 2016(Akram et al, , 2017Ding et al, 2014)). Canonical correlation analysis (CCA) also reduces dimensionality by finding separate linear transformations for the stimulus as well as neural responses, such that in the respective projected subspaces, the neural response and the stimulus are maximally correlated (de Cheveigné et al, 2018a,b;Dmochowski et al, 2018;Hotelling, 1936).…”
mentioning
confidence: 99%
“…The association between the fMRI data and the deep features fc7 (see multivariate linking box in Figure 1) can be learnt using multivariate linking methods. Canonical Correlation Analysis (CCA) [23] is often used in this respect [40,41,42,43,44], as it allows projecting one dataset onto another by means of linear mapping, which can be further used for categorical discrimination and brain model interpretations.…”
Section: Linking Methodsmentioning
confidence: 99%
“…We demonstrated that the brain responses to naturalistic speech could be better predicted by including a phonemebased stimulus representation, and by extracting speech-related information from the recorded EEG signals using a GEVD approach combined with standard multivariate TRF (Crosse et al, 2016). This method, which is closely related to the CCA-based method proposed by de Cheveigné & Parra (2014) and Dmochowski, Ki, DeGuzman, Sajda, & Parra (2018), allows substantially increasing the EEG prediction, with a correlation of around 0.1 reached using the delta EEG band and a high-level speech representation. Moreover, we here showed that the inclusion of this linear spatial mapping allows removing the impact of manual channel selection on the performance by automatically weighting channels in a data-driven way.…”
Section: Consistent With DImentioning
confidence: 95%